English as a Second Language (ESL) Learner's Perceptions of the Difficulties in Oral Commentary Assessment / Wan Nuur Fazliza Wan Zakaria and Siti Shazlin Razak - Wan Zakaria, Wan Nuur Fazliza; Razak, Siti Shazlin (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2016)
The present study attempts to investigatethe Diploma students’ perceptions onthe difficulties they face in oral commentary as a form of assessment from three perspectives: learners’ personal traits, oral presentation skills and audience and lecturer. The respondents, who are currently taking English as a Second Language (ESL) course, ELC230 Integrated Language Skills: Writing, are 65 Part 3 Diploma students of Universiti Teknologi Mara (UiTM) Kelantan. They are randomly selected using random sampling technique, and they are required to respond to a set of five-point Likert scale questionnaire which consists of 38 items. The data is analysed using SPSS 19.0. The findings indicate that these ESL learners do moderately experience difficulties in oral commentary assessment with the average mean valueof3.53